Identity and the young English language learner - Day, Elaine Mellen (Bilingual education and bilingualism, 2002)
This longitudinal, ethnographic case study examines the language socialization experiences of Hari, a Punjabi-speaking English language learner integrated in a mainstream kindergarten classroom in an urban area of British Columbia, Canada. The study uses sociocultural and critical/poststructural theoretical perspectives to explore the intimate connection between learning, identity and social membership in Hari's learning path. The book highlights the political and affective dynamics of classroom relationships and their unconscious as well as conscious dimensions and should be of interest to all researchers, students, and educators involved with minority language children in educational contexts.